Colorimetric screening of mitragynine in biological and non- biological sample matrices for detection of forensic drugs - Zamri, Nur Shahida Mohamad (2020)
New psychoactive substances (NPS) can be defined as the substance of abuse or been known as 'legal high' or 'bath salts' according to the United Nation on Drugs and Crime (UNODC). Listed as NPS, mitragynine is a compound that has the opioid type properties that are present in Mitragyna speciosa plant or also known locally as ketum plant. Ketum' is a plant in the coffee family plant native to Southeast Asia including Malaysia, Thailand, Indonesia and Burma. Generally, this study focuses on investigating mitragynine colour reaction towards Van Urk reagent in biological and non-biological samples by visual observation and spectrophotometric analysis. Colour test with Van Urk reagent and colorimetric analyses (mobile application and microplate reader spectrophotometer) were conducted for detection of mitragynine in various sample matrices (biological and non-biological). The detection of mitragynine from decoction, concoction and powder (non-biological) samples with Van Urk reagent produced a fast and successful reaction of colour change to pink. However, as for biological sample such as urine, direct detection using Van Urk reagent shown inconclusive result which there was no apparent of pink colour change. Extraction needs to be performed on biological samples, precisely urine sample in order to produce a better result. To summarise, the colorimetric analysis of multiple-sample measurement using a smartphone a detector was not ideal. RGB values that measured was not consistent even though the standardised image capture system was built to capture the image of all the samples. Furthermore, spectrometric analysis using microplate reader spectrophotometer also did not convey satisfactory result.